DRUG UTILIZATION STUDY OF PSYCHOTROPIC DRUGS IN PSYCHIATRY OUTDOOR PATIENTS AT A TERTIARY CARE HOSPITAL - PRANAB DAS; NIVEDITA SAHA; DOLLY ROY (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The objective of this study was to evaluate the drug utilization pattern of psychotropic drugs prescribed in patients as per the World Health Organization core prescribing indicators. Methods: The investigation examined all patient medical records who visited the outpatient department of the Department of Psychiatry, Silchar Medical College and Hospital between September 2023 and March 2024. The prescriptions were analyzed for indicators of drug use such as the quantity of drugs prescribed, generic name prescriptions, essential drug list prescriptions, antibiotics prescribed, injection prescribed, and the percentage of polypharmacy. Results: A total of 600 prescriptions were examined. The most common type of psychotropic drug administered was antidepressants. Psychotropic drugs were administered on an average of 1.64 times per prescription. The proportion of generic names was 98.88%; the proportion of prescription encounters involving an injection was 3.33%; the proportion of psychiatric medications prescribed from the National List of Essential Medicines (NLEM) was 62.53%; and the proportion of polypharmacy was 5.5%. Conclusion: This study setting performed well in terms of the proportion of prescriptions that included injections and antibiotics; nevertheless, it fell short of recommendations in terms of NLEM drugs, generic drugs, and minimizing polypharmacy.